No Effects of Mental Fatigue and Cerebral Stimulation on Physical Performance of Master Swimmers - Penna, Eduardo Macedo; Filho, Edson; Campos, Bruno Teobaldo; Ferreira, Renato Melo; Parma, Juliana Otoni; Lage, Guilherme Menezes; Coswig, Victor Silveira; Wanner, Samuel Penna; Prado, Luciano Sales (Frontiers in Psychology, 2021)
Mental fatigue is a psychobiological state caused by extended periods of cognitive effort, and it has been observed that mentally-fatigued athletes present impaired physical performance. Different ergogenic aids have been proposed to counteract the deleterious effects of mental fatigue, but whether brain stimulation can counteract mental fatigue is still unknown. This scenario is even more obscure considering the effects of these interventions (mental fatigue induction and brain stimulation) in a very experienced population consisting of master athletes. Method: Ten master swimmers (30.3 ± 5.8 years old and 14 ± 8 years of experience) participated in the study. They underwent four experimental conditions before an 800-m freestyle test: mental fatigue with brain stimulation; mental fatigue without brain stimulation; absence of mental fatigue with brain stimulation; and absence of mental fatigue and no brain stimulation. Mental fatigue was induced by a cognitively-demanding Stroop Color Test, whereas stimulation was applied on the temporal cortex. After that, the athlete’s swan 800 m as fast as possible and provided their ratings of perceived exertion (RPE) every 200 m. Results: Mental fatigue was effectively induced, as evidenced by a greater fatigue perception and more errors in the last blocks of the cognitive task. Mental fatigue induction did not influence performance (time to complete the swimming trial) and RPE. Similarly, brain stimulation failed to change these two parameters, regardless of mental fatigue. Conclusion: The prolonged physical performance of experienced master athletes is not influenced, under the present conditions, by mental fatigue induction, cerebral stimulation, and their association.